Konsep Jihad dalam Hukum Islam - Ilham, Ade Ihwana; Salsabila, Shabrina Syifa; Rahman R., Abd. (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to understand and analyze the concept of jihad in Islam. This journal writing method uses the Normative legal method using a conceptual approach. The study results show that jihad in Islam has a wider scope than war activities. It includes war and spending wealth and all efforts in order to support the religion of Allah SWT, fighting in the face of lust and Satan. Jihad is not only limited to carrying out war or violence, but there are many ways that Allah has given us to play an active role in the context of this form of worship. Jihad carried out in a peaceful form such as preaching, seeking knowledge, taking part in peace conferences is a beautifully conceptualized jihad that will minimize losses between both parties, especially Muslims.